The Cost of an Operating Room Minute for Heart Valve Procedures - Eugene A. Grossi; Matthew Moore; Peter J. Mallow; John A. Rizzo (Journal of Health Economics and Outcomes Research)
**Background:** Heart valve disease is very common, with approximately 5 million people diagnosed with this disease annually in the United States. There has been substantial innovation in the technologies and techniques of surgical repair and replacement over the past decade. However, there is little information that allows the potential time savings associated with these technologies and techniques to be quantified from the hospital perspective.